Utilisation of pulp and paper industry wastes as raw materials in cement clinker production - Castro, F. (2009)
The present work assesses the incorporation of grits and dregs, both wastes from cellulose and paper making industry, in cement clinker production. Industrial trials were developed with conventional raw clinker, used as a reference material and with the addition of grits and dregs, 0.25% and 0.13%, respectively. All raw meals were fired at 1400?1500°C. Chemical composition of the final mixtures, gaseous emissions quality during clinker production and leaching behaviour of the final products were evaluated. The results show that such incorporation could be an effective process for waste management from both the environmental and economic points of view.